Power-load curves in an elite weightlifter. A case study - Flores de Frutos, F. J.; Sedano-Campos, S.; Redondo-Castán, J. C. (Revista Internacional de Ciencias del Deporte, 2017)
Findings from mechanical power data can make a significant difference in the performance of athletes in weightlifting if it is properly understood by coaches. The purpose of this study was to examine the power-load (P-L) curve in the snatch, clean, back jerk and jerk of an international-level Spanish weightlifter. Four testing sessions were conducted in the present work. Session 1: estimating snatch and clean 1RM (1 repetition maximum); Session 2: power assessment of the snatch and clean across a spectrum of loads (30% to 100%) of the predetermined 1RM; Session 3: estimating back jerk and jerk 1RM; Session 4: power assessment of the back jerk and jerk across a spectrum of loads (30% to 100%) of the predetermined 1RM. The highest peak power output (Pmax) was reached with loads of 90% of 1RM in each exercise tested, which demonstrated this percentage to be the optimal load (Pmax load) to train power development during weightlifting exercises.